Adangiyah: Philosophy of Art in Tradition and Modernization - Bambang Sunarto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2021)
Dewa Ruci's journal on this edition is felt so special. Since volume 15 has been eager to target a wider audience. Many scientific idiographic concepts are important and need to be known by international readers. This edition is proud to present the most widely written articles by postgraduate students and lecturers from the Indonesian Institute of the Arts Surakarta, Universities of Education from Surabaya, and Malang (East Java). What is special about this edition of this journal is the participation of the second author, who comes from various countries who are very encouraging to the first author. The participating writers from abroad are Adzrool Idzwan Ismail (Malaysia), Michiyo Yoneno Reyes (Japan), Nazima Rangwala Kalita (India), Lee Yong-Shik (South Korea), Jody Diamond (United States).We above appear to have six collaboratively written articles to publish on this occasion. The first author, Soerjo Wido Minato, wrote an article entitled “Art, Nature, and Culinary As Leverages for Village Branding at the Foot of the Mountain.” He discussed that coastal tourism and coastal villages have always been attractions, especially mountain villages that have succeeded in branding themselves as tourist villages. The Malang State University research team conducted research activities to support the preparation of Benjor Village to become a tourist village. An effective strategy for branding Benjor Village as a tourist village at the foot of the mountain is to synergize art, nature, and culinary arts in logos, songs, dances, taglines, videos, and social media.Next is Yulela Nur Imama's article entitled "Masak, Macak, Manak” at this time through challenge-based research on the creation of Nol dance," discussing 3M (cooking, preening, give birth) as cultural values for Javanese women. This study aims to determine the existence and relevance of these 3M values in dance works and how these values must be maintained. Tari Nol interprets 3M's cultural values.Hanna Medita wrote the article “Self Me: interpretation of self-injury in the context of healing,” discussing modernization that affects human needs. Self Me is a work inspired by the author's experience of self-injury which is very common among teenagers towards adulthood. Many symptoms are very likely to affect one's mental health. The work of Self Me gives a message about the importance of knowing self-injury early on and knowing what the symptoms of self-injury are.Rian Prasetya's article entitled "Color Formation of Musical Compositions of Children's Choir "Vocalista Angels" discusses the choir resulting from intensive training in various competitions in the Vocalista Angels (VA) group. The group emphasizes unique performance with sound color processing that deviates from the conventions of music theory. At the heart of quality processing at VA is building a distinctive tone of voice, trying to avoid musical tendencies based on classical vocal theory. An important element to form distinctiveness is a musical work that puts forward the method of wording, processing articulation, resonance, and intonation.Izam Ismail wrote the article "Media Adaptation of Mask Making in Malang: Study of Functional and Process for Making Fiber Masks" which discusses the adaptation made by changing the media without changing the shape and visuals that appear in Topeng Malang. The mask in the Malang Mask performance is a sacred form used by dancers by bringing the Panji character into the show. Making fiber masks begins with practice, namely making molds without changing the shape and ornaments on Malang Masks.Harmanto’s article entitled "The Concept of Tumbuk in Javanese Gamelan Tuning" discusses the phenomenon of musical mash in the Javanese karawitan tradition. Tumbuk is more than just a scale between Sléndro and Pélog. Tumbuk acts as a synchronizer in frequency and range between notes and a tone coordinator or add-on in the tuning system. Tones that have the same frequency in the tone of nêm are nêm sléndro and nêm pélog, nêm sléndro and pélog stuff, and others.The last writer is Hasbullah, with an article entitled "The Meaning Of Bali Aesthetic Code In The Animated Film Si Uma." He discusses the meaning of the Balinese aesthetic code in the animated film "Si Uma." The animated film gives a message through semantic codes such as cloth poleng, which connotes a balance of life and perfection. The meanings found from studying the Balinese aesthetic code in the animated film “Si Uma” are beauty, concentration, and cultural identity.That is the essence of the issue of Volume 16 Number 2 (December Edition), 2021. Hopefully, the knowledge that has been present in this publication can spur the growth of fine arts and performing arts in international networks, both in the arts. Creation and in the scientific research of art in general. We hope for the development of fine arts and arts.Thank you